2006
DOI: 10.1370/afm.390
|View full text |Cite
|
Sign up to set email alerts
|

State Anger and the Risk of Injury: A Case-Control and Case-Crossover Study

Abstract: PURPOSE Previous studies have examined anger at a given moment (state anger) and proxies for injury, or anger as a trait and injuries per se. Findings have been inconsistent. We sought to defi ne further the relationship between state anger and risk of injury. METHODSWe conducted a case-control and case-crossover study in all 3 emergency departments in 1 county in Missouri. Cases were patients seeking care for an acute injury. They were compared with 2 controls: the patient himself or herself 24 hours before, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In a combined case-control and case-crossover study Vinson et al found an association between state anger and risk of injury. In sub-analyses of different types of injury they reported increased risk estimates for fall injuries however statistically non-significant [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a combined case-control and case-crossover study Vinson et al found an association between state anger and risk of injury. In sub-analyses of different types of injury they reported increased risk estimates for fall injuries however statistically non-significant [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study among children aged 10–15 we have established that different kinds of emotional states, caused by peer victimization as well as perceived school failure have the potential to trigger unintentional injuries [ 12 - 15 ]. Another study has shown that although anger is strongly related to intentional injuries among adult men and women it does not seem to have the same impact on fall injuries [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…13 Anger is associated with intentional injury infl icted by another person, but not with fall and traffi c injuries.…”
Section: Quality Communication Anger and Depressionmentioning
confidence: 98%
“…Anger can be considered as state anger, an episode of anger occurring at a specified time, and as trait anger, an aspect of personality,[12] and is typically measured on four State Anger, Trait Anger, Anger In, Anger Out and Anger Control (STAXI) scales. [3]…”
Section: Introductionmentioning
confidence: 99%